Breeding biotechnologies - Kennedy, D. (International Laboratory for Research on Animal Diseases, 1994)
The first part of the paper describes embryo transfer in detail. The ILRAD herd of N'Damas has been increased using embryo transfer. The ILRAD experiment requiring the majority of the embryo transfer work is a project to locate the genes responsible for trypanotolerance in the N'Dama. Two generations of large full-sibling families obtained from crossing the trypanotolerant breed with a trypanosusceptible breed are being assembled. Four trypanosusceptible Boran donors were crossed with four of the original N'Dama bulls. This families are now being intercrossed to produce a further generation of full-sibling families with up to 40 calves in each family. The technique is also being used to produce haemopoietic chimaeras. An N'Dama embryo and a Boran embryo are implanted into a recipient cow in order to produce twins, one Boran and one N'Dama. Related developing technologies including in vitro production of embryos, transgenics, cloning, embryo sexing, and semen sexing are also summarised.